Festschrift in Honor of Norman K. Denzin : He Knew His Song Well - Chen, Shing-Ling S. (Studies in symbolic interaction, 2022)
Due to his major contributions in qualitative inquiries, Norman K. Denzin is regarded as 'the Father of Qualitative Inquiries.' Volume 55 of Studies in Symbolic Interaction is a compilation of writings published in his honor.